1981
DOI: 10.3758/bf03207359
|View full text |Cite
|
Sign up to set email alerts
|

Parafoveal information is not sufficient to produce semantic or visual priming

Abstract: Marcel (1978) has shown that semantic priming can occur in the lexical-decision task even if the prime is masked to the point at which its presence cannot be detected. The purpose of the present experiments was to determine if primes that begin four or five spaces to the right of fixation can also produce semantic facilitation even though they are very difficult to recognize. Experiment 1 showed that facilitation did occur when the parafoveal primes used in the subsequent experiments were presented foveally. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
3
23
1
Order By: Relevance
“…However, when the parafoveal stimuli are presented 2.3 ° or 3 ° from fixation, there is no difference between the condition in which the first 2 or 3 letters are preserved across the saccade and the condition in which all letters are preserved. It was suggested (McClelland & O'Regan, 1981;Paap & Newsome, 1981) that the basic pattern of results is obtained only when there is a limited target set, but Balota and Rayner (1983) demonstrated the robustness of the effect when a large stimulus set was used.…”
Section: Integration Of Information Across Saccadesmentioning
confidence: 99%
“…However, when the parafoveal stimuli are presented 2.3 ° or 3 ° from fixation, there is no difference between the condition in which the first 2 or 3 letters are preserved across the saccade and the condition in which all letters are preserved. It was suggested (McClelland & O'Regan, 1981;Paap & Newsome, 1981) that the basic pattern of results is obtained only when there is a limited target set, but Balota and Rayner (1983) demonstrated the robustness of the effect when a large stimulus set was used.…”
Section: Integration Of Information Across Saccadesmentioning
confidence: 99%
“…For examples of studies showing no parafoveal semantic processing, see Inhoff (1982), Inhoff and Rayner (1980), and Paap and Newsome (1981).…”
Section: Notesmentioning
confidence: 99%
“…These findings suggest that partial parafoveal information can be utilized in a variety of situations. The results of some experiments (McClelland & O'Regan, 1981;Paap & Newsome, 1981) have suggested that the facilitation observed in parafoveal naming studies by Rayner and his co-workers (Rayner, 1978;Rayner, McConkie, & Ehrlich, 1978;Rayner, McConkie, & Zola, 1980) was limited to situations in which the subject had strong expectations about what the parafoveal word would be. Most troubling was the implication that the priming from parafoveal information might be restricted to (unnatural) situations in which the set of words to be recognized (and named) was quite small.…”
Section: Is Information Integrated Across Fixations?mentioning
confidence: 99%